1984
DOI: 10.1289/ehp.8457241
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and excretion of 2-ethoxyethanol in the adult male rat.

Abstract: The routes of 14C excretion following the administration of a single oral 230 mg/kg body weight dose of 2-ethoxyethanol [ethanol-1,2-14C] or 2-ethoxyethanol [ethoxy-1-14C] to male Sprague-Dawley rats were investigated. Elimination of the 14C by the urinary route accounted for 76 to 80% of the dose within 96 hr. The main pathway of biotransformation is oxidation to the corresponding acid, with some subsequent conjugation of the acid metabolite with glycine. The major metabolites, ethoxyacetic acid and N-ethoxy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Since the half-life of 2-EAA in urine is on the order of 9 -24 h in rats (Cheever et al, 1984;Medinsky et al, 1990), exposures to EGEEA were conducted over a 5-day period to allow near steady-state conditions to be achieved. Preliminary modeling indicated that five exposures of 6 h/day should be sufficient.…”
Section: Model Predictions Of Rat Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Since the half-life of 2-EAA in urine is on the order of 9 -24 h in rats (Cheever et al, 1984;Medinsky et al, 1990), exposures to EGEEA were conducted over a 5-day period to allow near steady-state conditions to be achieved. Preliminary modeling indicated that five exposures of 6 h/day should be sufficient.…”
Section: Model Predictions Of Rat Datamentioning
confidence: 99%
“…However, the model predictions would be expected to include all 2-EAA- derived urinary metabolites, and the analytical method measures only 2-EAA. Experimental work (Cheever et al, 1984;Groeseneken et al, 1988;Sabourin et al, 1992;Kennedy et al, 1993) indicates that 2-EAA-derived urinary metabolites such as glycine conjugates may contribute 14 to 74% more 2-EAAderived urinary metabolites. The average in studies with male SD rats, the strain used in the study reported here, was 68% (Cheever et al, 1984).…”
Section: Model Predictions Of Rat Datamentioning
confidence: 99%
See 2 more Smart Citations
“…4.11 As with haemotoxicity, in vitro studies indicate that the acetic acid metabolite, not the parent glycol ether, is responsible for the testicular toxicity.4$ Following the administration of radiolabelled EE by gavage, EAA was the only radioactive compound found in rat testicular tissue. 49 Miller et 01.40 have demonstrated that the testicular toxicity of methoxyacetic acid (MAA) is qualitatively similar to that of its parent compound, ME. These results are consistent with in vitro findings that suggest the alkoxyacetic acid metabolite is the primary testicular toxin.…”
Section: Reproductivementioning
confidence: 99%